Water, land, and food: A swat-based approach to sustainable resource management in Tanralili Sub-Watershed South Sulawesi - A. Widiasari Maruddani; Suryansyah Surahman; Gilang Bayu Prawira (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2026)
The sustainable management of water, land, and food resources is crucial for food security in areas under environmental stress. This study focuses on the Tanralili Sub-Watershed in South Sulawesi, Indonesia, which faces soil erosion, water imbalance, and land degradation. The Soil and Water Assessment Tool (SWAT) was integrated with a geographic information system (GIS) to assess hydrological responses to land use dynamics and their impact on agricultural productivity. Spatial data, including a 2023 land use map, digital elevation model, soil parameters, and climate data, were processed for hydrological simulation. Model calibration and validation were performed using observed streamflow data to ensure accuracy. The results show high erosion rates (>3000 t.ha–1) and runoff in sub-watersheds with steep slopes and intensive farming, whereas forested areas demonstrated better infiltration and reduced sediment yield. Conservation strategies, such as reforestation, terracing, and water harvesting, were identified to improve irrigation efficiency by up to 20%. Integrated resource management is projected to enhance water availability, reduce land degradation, and support sustainable food production. These findings provide a scientific basis for policy and demonstrate the relevance of SWAT modelling in watershed management.